Bank Capital and Uncertainty - Valencia, Fabian (Washington, D.C. : International Monetary Fund, 2010)
An important role for bank capital is that of a buffer against unexpected losses. As uncertainty about these losses increases, the theory predicts an increase in the optimal level of bank capital. This paper investigates this implication empirically with U.S. Commercial Banks data and finds statistically significant and robust evidence supporting it. A counterfactual experiment suggests that a decline in uncertainty to the lowest level measured in the sample generates an average reduction in bank capital ratios of slightly over 1 percentage point. However, I also find suggestive evidence that the intensity of this precautionary motive is stronger during recessions. From a policy perspective, these results suggest that the effectiveness of countercyclical capital requirements during bad times will be undermined by banks desire to hold more capital in response to increased uncertainty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet